PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION PADA KARYAWAN OFFICE PT CIPTA NUGRAHA CONTRINDO - Putri, Ayu Rachmawati; Waskito, Meindro (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2021)
The purpose of this study was to determine the effect of compensation and job satisfaction on turnover intention of office employees at PT Cipta Nugraha Contrindo, carried out on all office employees, with a sample of 64 employees using a saturated sample. The method of data collection by distributing questionnaires to obtain primary data with data analysis used by simple regression analysis with regression equations, correlation coefficients, coefficients of determination and hypothesis testing (t test) using the SPSS 26 program. Based on the results of data analysis and hypothesis testing that has been conducted shows that partially compensation (X1) has a low, negative and significant effect on turnover intention (Y). Likewise, job satisfaction (X2) partially shows that there is a low, negative and significant influence on the turnover intention (Y) of PT Cipta Nugraha Contrindo office employees.